Climate change impacts of the UK Department for International Development’s (DfID) commercial agriculture portfolio: Findings and recommendations to the Africa Regional Department - Costa, Ciniro (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This presentation was given to DfID (Department for International Development) by Ciniro Costa Jr, CCAFS, on November 25, 2020.